Improving the Performance of Bumdes and UMKM Empowerment in Trombol Village - Indrajat, Heri; Maulana, Fathoni Akbar; Puspitasari, Dea Ayu; Kusuma, Evita Rizki; Rahmadani, Fitria; Mufidah, Aulya Fathin; Guston, Muhammad Rayhan; Kurniasih, Arrum Hamidah; Prasasti, Dania; Febriani, Sinta; Novika, Revi Gama Hatta (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2025)
This research aims to address the problem of stagnancy of Trombol Village's MSMEs development. In general, MSMEs contributes economic growth; but does not applicable in Trombol. By using qualitative research methods and assisted by a grounded theory approach, the main problems can be developed with other questions that are linear. Fluctuating demand is the root of the problem. Thus, market share improvement to be fixed. However, the next problem would be came up when try to implement digital marketing because lack of infrastructure and/or knowledge. New innovations that should have positive implications generated its opposition. Village-owned enterprises developed to address market share problems that happens in the MSME. Village-owned enterprises to be a dropshipper which made it does not need to provide any goods. MSME’s products have been registered with village-owned enterprises; there are dominated by snack. Stimulant with this, village-owned enterprises taught about social media analytics tools to look at raw data on social media, reading trends, and making decisions. To be a catalyzer, the creation of social media accounts on Facebook and Instagram were launched. A wage is a reward for village-owned enterprises employees who can sold their products. The MSMEs are allowed to register their products with the village-owned enterprises in the future. Last but not least, simple accounting manager is educated to make financial reports that will stimulate the trust of other parties, and monitor the political will of business policy. The problem of economic growth in Trombol Village, poverty reduction, and joblessness would occur progressively.